SACRIFICE FOR THE SAKE OF SPORTS AS A VICTIM PROPERTY OF AN ATHLETE'S PERSONALITY - Baturkina, G.V.; Budyakova, T.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the role of sacrifice for the sake of sport in maintaining the stability of the athlete's personality. Methods and structure of the study. Active interview, case method and content analysis were used as methods. 40 interviews of athletes were analyzed, of which 30 were taken from the media, 10 were conducted by the authors of the study. In addition, 14 cases were analyzed in which elements of sacrificial behavior in athletes were recorded. Results and conclusions. Six thematic groups of judgments have been identified that differ in content in terms of understanding the phenomenon of sacrifice among athletes. Among them: “avoidance of sacrifice”, “condemnation of sacrifice”, “pragmatic attitude towards sacrifice”, “understanding of sacrifice as a mission, as heroism”, etc. It is shown that not all variants of sacrifice ensure the stability of the athlete's personality. In particular, such varieties of sacrifice as "fictitious sacrifice" and "sacrifice for the sake of fear" perform a negative function.